The Consumer Confidence Clock - Gutiérrez-Espeleta, Edgar E. (2010)
Measuring the consumer confidence via an index (ICC) allows the “pulse taking” of the dynamics of the domestic economy in a country, for a given period of time. This index has “leading” properties which allows the anticipation of undesirable situations in the evolution of the national economy. The “Clock of the consumer confidence” is a visual tool that enables the appreciation of the evolution of the distinct perception of Costa Rican households towards national economy in a longer period of time. Thus, four scenarios can be drawn ranging from optimism and summit to pessimism and downfall. Obviously, societies with not only a good appreciation of its actuality but also of its future could be found in the first set of scenarios. This tool should be considered into the traditional analysis of national economic performance